An appearance-driven method for converting polygon soup building models for 3D geospatial applications - Chen, Kan (2019)
Polygon soup building models are fine for visualization purposes such as in games and movies. They, however, are not suitable for 3D geospatial applications which require geometrical analysis, since they lack connectivity information and may contain intersections internally between their parts. In this paper, we propose an appearance-driven method to interactively convert an input polygon soup building model to a two-manifold mesh, which is more suitable for 3D geospatial applications. Since a polygon soup model is not suitable for geometrical analysis, our key idea is to extract and utilize the visual appearance of the input building model for the conversion. We extract the silhouettes and use them to identify the features of the building. We then generate horizontal cross sections based on the locations of the features and then reconstruct the building by connecting two neighbouring cross sections. We propose to integrate various rasterization techniques to facilitate the conversion. Experimental results show the effectiveness of the proposed method.